Мовне бачення Всевишнього в поезії Богдана Ігоря Антонича - Маленицька, Ольга; Malenytska, Olha (Східноєвропейський національний університет імені Лесі Українки, 2014)
У статті проаналізовано мовні засоби творення образу Бога в поетичній спадщині Богдана Ігоря Антонича. Досліджено лексику найменувань, синонімічні ряди й перифрази, художні означення, синтаксичні особливості порівнянь, специфіку метафоричності й численні стилістичні фігури, посередництвом яких поет оригінально змальовує осіб Святої Трійці, не порушуючи при цьому канонів християнства. Preservation of the national identity of the people depends on the measure of self-awareness features of the mentality of the people. Individual writer's view of the world is an objective display of such features. Poetry Bogdan Igor Antonovich, presenting features of the spiritual world of one of the ethnic groups of Ukrainians,however, shows the linguistic skills of the writer.The study of linguistic identity created by a poet of images of the Holy Trinity assures used in a wide range of funds. Different vocabulary, synonyms series epithets, metaphors, a variety of syntactic organization of comparison, paraphrasing, graduation and apostrophe, allusion and amplification are equally subject to BI Antonovich, presenting his special ability to combine the richness of the traditional impressionistic moderation.
Language vision of God in the poetry of Bohdan Ihor Antonych
Keywords: індивідуальна мовна картина світу; мовні засоби; лексика; синоніміка; тропи; метафоризація; синтаксична конструкція; стилістичні фігури; individual language picture of the world; language tools; vocabulary; synonymy; trails; metaphorization; stylistic figures